Real Time Enterprise – A new approach to competition - Galewski, Tomasz; Kuśmierczyk, Paweł (Publishing House of the Wrocław University of Economics, 2009)
In the classical theory of economics a firm was modelled as the economic agent having perfect knowledge about all its environment. This knowledge involved the complete information on its customers, its competitors and all the relevant aspects of economic and political system. Moreover, in this theory the firm did not have any problems with the processing of such an amount of information; it made optimal decisions in “zero time.” A good example of such a theory can be the perfect competition, still one of the most popular economic models. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 172-180